ANALYSIS OF THE INFLUENCE OF GRAIN SIZE ON INCREASING CALORIES OF LOW RANK COAL USING THE BROWN COAL UPGRADING METHOD: ANALISIS PENGARUH UKURAN BUTIR TERHADAP PENINGKATAN KALORI BATUBARA PERINGKAT RENDAH DENGAN MENGGUNAKAN METODE UPGRADING BROWN COAL - Krisanto Yardin Panggeso; Windhu Nugroho; Shalaho Dina Devy; Agus Winarno; Revia Oktaviani (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2023)
Upgrading Brown Coal aims to reduce the water content in coal so that the calorific value of coal will increase. The methods used in the upgrading process are inherent moisture, volatile matter, ash content, and fixed carbon. The results after upgrading the calorific value of coal by varying the coal size and heating time showed that the most optimum coal calorific value was in sample B1 size 100 mesh with a mixture composition of 50 grams of coal, 100 ml of used cooking oil and 100 ml of diesel, namely with a calorific value of 7388. 86 Cal/gr. The greater the composition value of used cooking oil and diesel, the smaller the inherent moisture value. In sample A with a mesh size of 50 with a composition of 50 grams of coal, 100 ml of used cooking oil, and 100 ml of diesel, the inherent moisture value was 6.7132%. Sample B with a mesh size of 100 with a composition of 50 grams of coal, 100 ml of used cooking oil, and 100 ml of diesel obtained an inherent moisture value of 6.9858%. The smaller the composition of used cooking oil and diesel, the smaller the ash content value, in the sample the mesh size is 50 with a value of 2.0771%, and in sample B the mesh size is 100 with a value of 1.9070%. The effect of coal size on the upgrading process is to increase the maximum calorific value of the 50 mesh size of the coal.